Excretion of Dietary Cow's Milk Derived Peptides Into Breast Milk - Picariello, Gianluca; De Cicco, Maristella; Nocerino, Rita; Paparo, Lorella; Mamone, Gianfranco; Addeo, Francesco; Berni Canani, Roberto (Frontiers in Nutrition, 2019)
Nanoflow-HPLC-tandem mass spectrometry (MS/MS) was used to analyze the peptide fraction of breast milk samples collected from a single non-atopic donor on different days (ten samples) after receiving an oral load of cow’s milk (by drinking 200 mL of bovine milk). In addition, breast milk was sampled from the same lactating mother over a 6-h period at 5 time points after drinking cow’s milk. We aimed to trace the intra-individual variability and to define a time profile of the excretion of dietary peptides into breast milk. Overall, 21 peptides exclusively originating from both bovine caseins and whey proteins with no match within the human milk proteome were identified in the breast milk samples. These peptides were missing in the breast milk obtained from the mother after a prolonged milk- and dairy-free diet (three samples). The time course of cow’s milk-derived β-Lg f(125-135) and β-casein f(81-92) in breast milk was determined from the MS ion intensity of the peptide signals. No intact cow’s milk gene products were detected by HPLC-MS/MS analysis and Western blotting with anti-β-Lg antibody, but dot-blot analysis confirmed the occurrence of β-Lg fragments in the enriched peptide fraction of breast milk. These data suggest shifting the analytical perspective for the detection of dietary food allergens in breast milk from intact proteins to digested peptide fragments. The possible sensitization and elicitation potential or the tolerogenic properties of such low amounts of dietary peptides for the breastfed newborns remain to be explored.